ANALISIS PENGARUH LONGTERM RELATION, INFORMATION SHARING, COOPERATION, INTEGRATION PROCESS TERHADAP KINERJA SUPPLY CHAIN MANAGEMENT (Studi pada UKM Kabupaten Gresik) - Aziz, Rasyadan Tahrizi; Dwiyanto, Bambang Munas (Diponegoro Journal of Management, 2017)
This study motivated by the phenomena gap that occurred on small and middle enterprise (UKM) which is engaged in the food processing industry in Gresik. This study aims to examine the performance of Supply Chain Management which include focus on independent variables longterm relation, information sharing, Cooperation, Integration Process.The population in this study are all the small and middle enterprise’s business owner in the food processing industry (IKM) in Gresik. Data collection method used is the method of sampling the sample amount to 106 respondents. The analytical method used is multiple regression.Based on statistical data analysis, the indicators in this study are valid and reliable. Sequentially based on the highest up to the lowest effect variable is the variable of longterm relation, information sharing, Integration Process, Cooperation. The result of the study found that three of all the independent variables are significant positive effect on the dependent variable while another variable (Cooperation) is significant negative.